Impact of renin–angiotensin system inhibitors on clinical outcomes in patients with severe aortic stenosis undergoing transcatheter aortic valve replacement: an analysis of from the PARTNER 2 trial and registries. (11th November 2019) - Chen, Shmuel; Redfors, Bjorn; Nazif, Tamim; Kirtane, Ajay; Crowley, Aaron; Ben-Yehuda, Ori; Kapadia, Samir; Finn, Matthew T; Goel, Sachin; Lindman, Brian R; Alu, Maria C; Chau, Katherine H; et al.
Abstract: Aims: Left ventricular pressure overload is associated with activation of the cardiac renin–angiotensin system, which may contribute to myocardial fibrosis and worse clinical outcomes. We sought to assess the association between treatment with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) at baseline and clinical outcomes in patients with symptomatic, severe aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR) in the PARTNER 2 trial and registries. Methods and results: A total of 3979 intermediate, high, or prohibitive risk patients who underwent TAVR in the PARTNER 2 trial and registries (excluding the valve in valve registry) were included in the study. Clinical outcomes at 2 years were compared according to baseline ACEI/ARB treatment status using Kaplan–Meier event rates and study-stratified multivariable Cox proportional hazards regression models. Sensitivity analysis was conducted using propensity score matching. Of 3979 patients who were included in the current analysis, 1736 (43.6%) were treated and 2243 (56.4%) were not treated with ACEI/ARB at baseline. Treatment with ACEI/ARB was associated with lower 2-year all-cause mortality (18.6% vs. 27.5%, P  < 0.0001), cardiovascular mortality (12.3% vs. 17.9%, P  < 0.0001), and non-cardiovascular mortality (7.2% vs. 11.7%, P  < 0.0001). Angiotensin-converting enzyme inhibitor/ARB treatment at baseline remained independently associated with a lower hazard of 2-year all-cause and cardiovascular mortality after multivariable adjustment, and propensity score matching. Conclusion: In a large cohort of patients with severe symptomatic AS from the PARTNER 2 trial and registries, ACEI/ARB treatment at baseline was independently associated with a lower risk of 2-year all-cause and cardiovascular mortality.